CURIPOD Y SU APORTE EN EL PROCESO DE ENSEÑANZA-APRENDIZAJE DE LOS ESTUDIANTES DE BACHILLERATO TÉCNICO EN INFORMÁTICA, SECCIÓN VESPERTINA DE LA UNIDAD EDUCATIVA SAN JUAN, PERIODO ACADÉMICO ABRIL-AGOSTO 2024. - CAMPOS VERA CECILIA MABEL (2024)
The central objective of this research is to determine the contribution of Curipod in the teaching-learning process of technical high school students in computer science, afternoon section of the San Juan Educational Unit, academic period April-August 2024, since, this tool complemented With AI it is revolutionizing the way of teaching with the possibility of improving the routine of class syllabi. The methodology is supported by the descriptive and exploratory research type, through a mixed approach, through which information will be obtained according to the data collection techniques that were the survey and the focus group, where the first was divided into 10 closed questions that were addressed only to 180 students selected through the sample and the second was made up of 5 open questions addressed only to teachers, through which results were obtained that allowed identifying the existing findings in the educational environment according to the use by Curipod. Based on all the processes applied in the study correctly, the objectives set at the beginning of the research were met, demonstrating positive results according to the functionality and activities that allow emerging technologies to be carried out in the classroom. Keywords: Curipod, student, teaching-learning, interaction